2013
DOI: 10.1177/1753425913506949
|View full text |Cite
|
Sign up to set email alerts
|

TNFR2 maintains adequate IL-12 production by dendritic cells in inflammatory responses by regulating endogenous TNF levels

Abstract: Sepsis-induced immune reactions are reduced in TNF receptor 2 (TNFR2)-deficient mice as previously shown. In order to elucidate the underlying mechanisms, the functional integrity of myeloid cells of TNFR2-deficient mice was analyzed and compared to wild type (WT) mice. The capacity of dendritic cells to produce IL-12 was strongly impaired in TNFdeficient mice, mirroring impaired production of IL-12 by WT dendritic cells in sepsis or after LPS or TNF pre-treatment. In addition, TNFR2-deficient mice were refrac… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 45 publications
0
10
0
Order By: Relevance
“…Although there was no significant change in the expression of IL‐12, a Th1‐polarizing cytokine, we detected a significant increase in the expression of TNFα from DCs stimulated with both LPS and hPS compared to cells treated with LPS alone. TNFα is required for optimal production of IL‐12 by DCs 34,35. In addition, hPS increased the expression of both IL‐12 and TNFα in dendritic cells stimulated with Der p1 or TSLP that are known to induce Th2 immunity in the context of allergic asthma.…”
Section: Discussionmentioning
confidence: 99%
“…Although there was no significant change in the expression of IL‐12, a Th1‐polarizing cytokine, we detected a significant increase in the expression of TNFα from DCs stimulated with both LPS and hPS compared to cells treated with LPS alone. TNFα is required for optimal production of IL‐12 by DCs 34,35. In addition, hPS increased the expression of both IL‐12 and TNFα in dendritic cells stimulated with Der p1 or TSLP that are known to induce Th2 immunity in the context of allergic asthma.…”
Section: Discussionmentioning
confidence: 99%
“…TNFR1 exists constitutively on most cell surfaces and functions when activated by trimerized TNF. TNFR2 is expressed, in a highly regulated way, on the surface of several cell types, such as immune cells, endothelial cells, epithelial cells and neuronal cells (Martin et al, 2014). Activation of TNFR2 leads to signal pathways that are different to that of TNFR1 (Hehlgans and Pfeffer, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…In previous work, we and others demonstrated impaired functions of myeloid cells and B cells following sepsis [14,16,[19][20][21]. In addition, T cell dysfunction was demonstrated and accompanied by increased numbers of Treg [22][23][24].…”
Section: Discussionmentioning
confidence: 80%
“…The model of cecal ligation and puncture (CLP) is a clinical relevant mouse model for poly-microbial septic peritonitis [10]. In this experimental model for sepsis, we were previously able to demonstrate the above described sepsis-derived immune deviations such as reduced cytokine production [11][12][13], impaired functionality of dendritic cells (DC) [14], and the increased ratio of Treg in the CD4 þ T cell population [15]. Further, we showed that the primary B cell response in septic mice was impaired [16].…”
Section: Introductionmentioning
confidence: 99%